2013
DOI: 10.1177/1089253213510748
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Diastolic Dysfunction and Heart Failure With Preserved Ejection Fraction

Abstract: As the population ages, the incidence of patients presenting for surgical procedures with diastolic dysfunction and heart failure with preserved ejection fraction will rise. This review will discuss the most current and relevant information on the pathophysiology, treatment, and perioperative management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…HFPEF is a well-described entity with prevalence ranging from 1.1 to 1.5% [ 3 ]. Studies have reported mixed results for perioperative risk in patients with HF and preserved LVEF [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…HFPEF is a well-described entity with prevalence ranging from 1.1 to 1.5% [ 3 ]. Studies have reported mixed results for perioperative risk in patients with HF and preserved LVEF [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diastolic heart failure is termed as HFpEF, and it is characterised by impairment in the distensibility of the myocardium, resulting in elevated ventricular diastolic pressures and thereby compromising the diastolic filling. [2,3] Post-operative diastolic dysfunction is hard to diagnose and often challenging to manage. [4] Due to lack of any definite clinical sign or specific test, diastolic failure is a diagnosis of exclusion and primarily depends on the combination of typical echocardiographic findings and elevated serum cardiac biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The ACC/AHA 2013 Class 1 recommendation for Stage III HFpEF is to maintain systolic and diastolic pressure with no specific mention of any agent. [2] We selected milrinone, a selective phosphodiesterase-III inhibitor, because of the following reasons. (1) It promotes diastolic function with a concomitant reduction in pulmonary and systemic vascular resistance, without a considerable increase in heart rate and myocardial oxygen consumption [6] and (2) It is less arrhythmogenic than dobutamine and therefore proved to be the most favourable inotropic agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last 2 articles are reviews of literature on diastolic dysfunction as it relates to the perioperative management of patients undergoing cardiac surgery. In “New Insights Into Diastolic Dysfunction and Heart Failure With Preserved Ejection Fraction,” 10 Dr Gelzinis focuses on the definition, symptoms, and diagnosis of diastolic heart failure and the perioperative management of patients with diastolic heart failure. The timing of this review is highly relevant.…”
mentioning
confidence: 99%